Empirical Study of Knowledge, Attitude and Practice towards to Radiation Health Hazards of Cell Phone: a Case Study on Medical Science Students - Marzieh Abbassinia; Mohsen Aliabadi; Safoora Karimi; Ebrahim Darvishi (Iranian Journal of Health, Safety and Environment, 2020)
The cell phone has become an essential part of life, however, in developing countries, knowledge and awareness of users about its adverse health effects have not enough increased. This study aimed to develop a questionnaire to investigate knowledge, attitude and practice regarding health hazards of the cell phone among college students. In this cross-sectional study, 230 graduate students of University of medical sciences located in Hamadan (western province of Iran) were participated, randomly. A developed self-administered questionnaire was completed by each participant to assess knowledge, attitude and practice regarding health hazards of the cell phone. The data was analyzed using SPSS 21. The results showed that the content validity ratio and the content validity index of the developed questionnaire were 0.915, 0.79, respectively. Cronbach (alpha), as a criterion of the reliability of the developed questionnaire, was also equal to 0.85. The scores of knowledge, attitudes and practice among the students were 7.95±2.5, 74.78±8.8, and 28.91±9.0, respectively. Relative to the maximum achievable scores, the acquired scores of attitudes was more acceptable than the others. Moreover, the acquired scores of the knowledge were more than the practice. The scientific controversy about health risks of the cell phones aggravated the public concerns about not well-known effects and consequently, it supported and motivated good attitude among student users. Moreover, it seems that the lack of proper knowledge about cell phone health hazards and protection principles can influence adequate practices. As low as reasonably achievable (ALARA) principle should be adopted for uses of the cell phone, while a major effort is done for monitoring of its new potential health impacts.